From Immune Dysfunction to Clinical Risk: Infections in Myelofibrosis - Laura De Fazio; Claudia Simio; Matteo Molica; Marco Rossi (European Journal of Haematology, 2026)
ABSTRACT Infectious complications are increasingly recognized as a crucial aspect of the clinical management of patients with Myelofibrosis. Infection susceptibility is multifactorial and reflects the interplay between disease‐related immune dysregulation, treatment‐associated immunomodulation, and patient‐specific factors such as age, comorbidities, and prior therapies. Myelofibrosis is characterized by a chronic inflammatory state and impaired innate and adaptive immunity, including dysfunction of natural killer cells, dendritic cells, and T lymphocytes. The introduction of JAKis has significantly improved disease outcomes, while these agents may further modulate immune responses through inhibition of the JAK–STAT pathway. Evidence from clinical trials and real‐world studies indicates that bacterial infections are common, while viral reactivations, particularly herpes zoster, represent a consistent complication of JAKi therapy. Opportunistic infections are less frequent but clinically relevant. In our view, infection risk in myelofibrosis should be considered an intrinsic component of disease biology and treatment. A risk‐adapted approach integrating baseline assessment, vaccination, and close clinical monitoring is warranted. Future efforts should focus on biomarker‐driven risk stratification and tailored preventive strategies to optimize outcomes in patients receiving JAKis.